Analisa Permasalahan Kedisiplinan dan Penataan SDM pada UMKM Pabrik Dimsum Qonita Food Store: Pengabdian - Muhammad Amin; Chandra, Lianni; Shofa, Ghaitsa Zahira; Saksono, Arif Lukman (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The Community Service Activity (KPB-PKL) aims to identify, analyze, and formulate Human Resource Management (HRM) issues to improve operational efficiency and business performance of the Small Medium Enterprise Qonita Food Store Dimsum Factory. The methodology utilized was a qualitative case study approach through Field Work Practice, relying on primary data collection methods: direct observation and semi-structured interviews with the owner and operational manager. Findings consistently revealed two critical HR constraints. First, a high degree of indiscipline regarding operational staff working hours, severely impacting the required consistency for B2B frozen food production. Second, limitation in specialized personnel, forcing the owner to handle crucial strategic non- production tasks like digital marketing. The cumulative impact includes decreased internal efficiency, heightened risk of failing to meet B2B client deadlines, and stunted market growth. The resulting solutions focus on strictly restructuring and enforcing working hours, establishing explicit job separation between administrative and service roles, and intensifying managerial supervision to cultivate a sustainable culture of work discipline.